A STUDY OF THE RELATIONSHIP BETWEEN STUDENTS’ PERCEPTIONS TOWARDS SCHOOL CLIMATE AND THEIR SATISFACTION AT SHEHONG MIDDLE SCHOOL, SICHUAN, CHINA - LUO, HONGBIN; YE, YAN (Scholar: Human Sciences, 2022)
This study aimed to investigate the relationship between students’ perceptions of school climate and their satisfaction at SheHong Middle School, Sichuan, China. By applying the Framework of school climates of Emmons, Haynes, & Comer (2002) and Maslow’s Hierarchy of Needs Theory (1987) theories, this study identified students’ perceptions towards school climate of six dimensions: 1) Order and Discipline 2) Fairness 3) Parent Involvement 4) Sharing Resources 5) Student Interpersonal Relationship 6) Student-Teacher Relationship, compared their perceptions according to 3 pieces of demographics. The results of this study indicated a significant relationship between students’ perceptions towards school climate and students’ satisfaction. The findings for research objective one revealed that the total mean score of the level of students’ perceptions of school climate was 3.43, which was interpreted as Moderate. The findings for research objective two showed that the total mean score of the level of students’ satisfaction was 3.46, which was interpreted as Moderate as well. The correlation result showed a positive relationship between students’ perceptions of school climate and students’ satisfaction. The researcher discussed the research findings and provided corresponding suggestions to related principals, teachers, and administrators at the selected school in Sichuan, China.